An optimized and versatile synthesis to pyridinylimidazole-type p38α mitogen activated protein kinase inhibitors. Issue 43 (9th September 2015) - El-Gokha, Ahmed; Laufer, Stefan A.; Koch, Pierre
Abstract : An optimized and diverse synthetic approach for the preparation of potent pyridinylimidazole-based p38α MAP kinase inhibitors is reported. Abstract : An optimized strategy for the synthesis of the potent p38α mitogen-activated protein kinase inhibitors 2-(2-hydroxyethylsulfanyl)-4-(4-fluorophenyl)-5-(2-aminopyridin-4-yl)imidazole (3 ) and 2-(2, 3-dihydroxypropylsulfanyl)-4-(4-fluorophenyl)-5-(2-aminopyridin-4-yl)imidazole (4 ) starting from 2-fluoro-4-methylpyridine is reported. In contrast to a previously published synthesis starting from 2-bromo-4-methylpyridine, the overall yield could be increased from 3.6% to 29.4%. Moreover, this strategy avoids the use of palladium as a catalyst and is more diverse and versatile. Using this optimized protocol, both enantiomers of potent inhibitor3 were synthesized. Biological data demonstrated that the ( S )-enantiomer is the two times more potent eutomer.